Minimization of Toxic Ions in Waste Water Using Emulsion Liquid Membrane Technique - A. Al - Hemiri, Adel; E. Mahmoud, Heaven (Iraqi Journal of Chemical and Petroleum Engineering, 2010)
In the present study, the removal of zinc from synthetic waste water using emulsion liquid membrane extraction technique was investigated. Synthetic surfactant solution is used as the emulsifying agent. Diphenylthiocarbazon (ditizone) was used as the extracting agent dissolved in carbon tetrachloride as the organic solvent and sulfuric acid is used as the stripping agent. The parameters that influence the extraction percentage of Zn+2 were studied. These are the ratio of volume of organic solvent to volume of aqueous feed (0.5-4), ratio of volume of surfactant solution to volume of aqueous feed (0.2-1.6), pH of the aqueous feed solution (5-10), mixing intensity (100-1000) rpm, concentration of extracting agent (20-400) ppm, surfactant concentration (0.2-2) wt.%, contact time (3-30) min, and concentration of strip phase (0.25-2) M . It was found that 87.4% of Zn+2 can be removed from the aqueous feed solution at the optimum operating conditions. Further studies were carried out on extraction percentages of other toxic metal ions (As+3, Hg+2, Pb+2, Cd+2) by using the same optimum conditions which were obtained for zinc ions except for the pH of the feed solutions. The pH values for best extraction percentages of arsenic, lead, and cadmium were (1, 10, 10) respectively. Maximum extraction percentage of (98.5, 95.5 and 93.8) was obtained for arsenic, lead, and cadmium respectively, while mercury was completely removed from the aqueous feed solution within the acidic pH range.